Brain Characteristics Noted Prior to and Following Cranial Orthotic Treatment. (18th August 2020) - DeGrazia, Michele; Ahtam, Banu; Rogers-Vizena, Carolyn R.; Proctor, Mark; Porter, Courtney; Vyas, Rutvi; Laurentys, Cynthia T.; Bergling, Emily; McLaughlin, Kara; Grant, Patricia Ellen
Objective: This case report aims to assess a potential association between cranial asymmetry, brain deformation, and associated developmental delay. Study Design: Two infants born at ≥37 weeks pursuing cranial orthotic treatment for severe Deformational Plagiocephaly (DP) (cranial vault asymmetry index >8.75%) underwent developmental assessment using Mullen Scales of Early Learning (MSEL) and non-sedated brain structural and diffusion magnetic resonance imaging (MRI) prior to and following cranial orthotic treatment. Results: In both infants with DP, tractography results revealed alterations in the white matter pathways of the brain. Both infants also had low to low/normal visual receptivity and fine motor skills. After cranial orthotic treatment, cranial asymmetry improved but did not completely resolve, tractography demonstrated a change toward normalized white matter pathways, and visual receptivity and fine motor skills improved. Conclusions: These preliminary findings suggest a potential link between DP, altered brain structures, and developmental assessment. Further investigation with a larger sample is warranted.